Experience of an entomological analysis of the breeding sites of Aedes aegypti and Culex quinquefasciatus in Cali, Colombia - GONZÁLEZ-OBANDO, RANULFO; GAMBOA, FEDERICO; PERAFÁN, ORLANDO; SUÁREZ, MARCO FIDEL; MONTOYA-LERMA, JAMES (Revista Colombiana de Entomología, 2007)
Larval sampling was carried out to evaluate the presence and population relationship between the vector of dengue, Aedes aegypti and Culex quinquefasciatus, vector of West Nile virus, in 537 sinks, located in 19 “comunas” (quarter associations) of the six SILOS (i.e. local health systems) of the city of Cali, Colombia. The mean positivity index (IS) for the sinks was 57.2% and 73.6% for each species, respectively. Although it was only a tendency, these values varied according to city social strata, and in all of the areas evaluated it was established that each species had a highly significant positive population correlation. In evaluating the relative importance of the city sinks in the production of A. aegypti, it was established that those breeding sites are equally or more important than intra or peridomiciliar breeding sites. The analysis of houses in 10 city blocks, including 62 street sinks in the nearby vicinity, revealed that intradomiciliar settings do not produce pupae. Assuming a constant adult survival rate of 0.80 per day, the number of females per block estimated for the sinks was greater than peridomiciliar breeding sites. For the street sinks, absolute density varied between 45 and 555 ( X= 200 female/block), while in the peridomiciliar settings it was only 0 and 69 ( X= 22 female/block).